Vosstanie - McDonald, Tracy (Canada : Chemodan Films, 2008)
A film on gender, violence and memory. In the fall of 1929, Joseph Stalin’s Soviet Union embarked on a violent drive for “wholesale collectivization.” Between the 22nd and 28th of February 1930, several thousand peasants from twenty villages in Pitelino rose up against the forces of collectivization. Unrest began in the village of Veriaevo and quickly spread to the neighboring villages of Gridino and Pyot. Peasants chased the collectivizers from their villages, resettled the dispossessed in their homes, and took back their livestock. Women were in the forefront of the movement. It took secret police and red army units well into March to crush the uprising. In the summer of 2004 and 2005 the filmmakers traveled to the villages of Pyot, Gridino and Veriaevo and interviewed women there about their memories of the rebellion. Their memories are living witness to the trauma of collectivization.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films